Bi-objective optimization of a standalone hybrid PV–Wind–battery system generation in a remote area in Tunisia. (December 2018) - Belouda, M.; Hajjaji, M.; Sliti, H.; Mami, A.
Abstract: In this article, the authors tackle a key topic of optimal sizing process for an hybrid system consisting of a Photovoltaic (PV) and wind systems associated to an electrochemical storage system, electrifying a typical remote zone in Tunisia. The main objective of this study is to optimally sizing the components of this system generation interacting with irradiations, wind speed and load cycles, especially for a standalone application. The study focuses on the optimal sizing a PV/Wind system associated to a battery bank as storage system for supplying an isolated area located in the north of Tunisia (Borj Cedria) . Obtained optimal solutions will be analyzed especially from the impact of the storage system point of view (deep discharges, cycles …) which is in intrinsic relation with system cost The first part of this article outlines the PV–wind turbine (WT)-Batteries generation system architecture and modeling. The optimal sizing of the system components satisfying two criteria by means of evolutionary algorithms is described in the second part of this article. The results are finally discussed from the point of view of the relevance of the system sizing and in terms of criteria satisfaction by analyzing two particular optimal configurations.